Pengaruh Struktur Kepemilikan Perusahaan Dan Karakteristik Komite Audit Terhadap Keinformatifan Laba Akuntansi - Maila Yanti; Salma Taqwa (Jurnal Eksplorasi Akuntansi, 2020)
Informativeness of accounting earnings is the ability of earnings in the level of decision making or return. This study aims to examine the effect of firm ownership structure , audit committee independence, financial expertise audit committee on earning informativeness. This research is a type of causal associative research with a quantitative approach. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2014-2018. The Sample was selected using a purposve sampling method with a total sample of 34 samples. The data used is secondary data from the company's annual report. The analytical method used is multiple linear regression analysis. The results showed that there was no influence of ownership structure and audit committee characteristics on earnings informativeness